YTaO4/Y₂Zr₂O₇ Dual-Phase Ceramics with Enhanced Vickers Hardness, Fracture Toughness and High Thermal Expansion Properties for Thermal Barrier Coating Applications - Ziyang Ruan; Zifan Zhao; Jing Feng (Metals)
Rare-earth tantalates (RETaO4) are considered as a type of emerging thermal barrier coating materials applied to the hot components of gas turbines and aerospace engines due to their excellent thermal stability, high-temperature fracture toughness, corrosion resistance and extremely low thermal conductivity. However, the relatively low hardness and thermal expansion coefficients may limit their service lifetime in a harsh engine environment. To address the current limitation of rare-earth tantalates and further optimize the mechanical and thermal properties, the defective fluorite-structured Y₂Zr₂O₇ (YZ) was introduced as a second phase into the YTaO4 (YT) matrix to form YT1−x–YZx (x = 0, 0.25, 0.5, 0.75, 1) composite ceramics in this work. The mechanical and thermal properties of YT1−x–YZx composite ceramics are significantly improved compared to pure-phase YTaO4 ceramics. The Vickers hardness of YT1−x–YZx (x = 0.25, 0.5, 0.75) composite ceramics is 9.1~11.3 GPa, which are 2~2.5 times higher than that of YTaO4 (4.5 GPa). Among them, YT0.75–YZ0.25 exhibits a maximum fracture toughness (3.7 ± 0.5 MPa·m1/2), achieving a 23% improvement compared to YTaO4 (3.0 ± 0.23 MPa·m1/2) and a 118% improvement compared to Y2Zr2O7 (1.73 ± 0.28 MPa·m1/2). The enhancement is attributed to the combined effect of the intrinsic strengthening of the second phase, as well as the residual stress and grain refinement caused by the introduction of a second phase. Additionally, the thermal expansion coefficients of YT1−x–YZx composite ceramics at 1673 K range from 10.3 × 10⁻⁶ K⁻1 to 11.0 × 10⁻⁶ K⁻1, which is also higher than that of YTaO4 (10.0 × 10−6 K−1). Consequently, the superior mechanical and thermal properties indicate that YT–YZ composite ceramics possess promising application prospects for thermal barrier coatings.